Impaired ovarian response to exogenous gonadotropins in female rat offspring born to mothers perinatally exposed to Bisphenol A - Santamaría, Clarisa Guillermina (2017)
The ovary is sensitive to disruption by the environmental estrogen Bisphenol A (BPA). Our aim was to investigate whether perinatal exposure to BPA (50 μg/kg day), orally administered, affects ovarian response to exogenous gonadotrophins (PMSG or PMSG + hCG) in prepubertal female offspring. An altered response to gonadotrophins was observed in BPA-exposed rats. Increased proportion of antral follicles, altered levels of ovarian steroidogenic enzymes, gonadotropin receptors, AR and ERβ were observed in PMSG group. Besides that, in response to PMSG + hCG, a persistent high Fshr mRNA expression and a decreased number of follicles with high expression of PR before ovulation were observed. After ovulation, there was an increase in antral atretic follicles, reduced Lhcgr mRNA expression and high serum levels of E2. Therefore, an early exposure to a low dose of BPA during perinatal period induces ovarian changes leading to an altered response to exogenous gonadotropin treatment later in life.